2019
DOI: 10.1109/access.2019.2942998
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Employee Participation in Enterprise Social Media on Their Job Performance

Abstract: This study focuses on employee involvement in enterprise social media (ESM) and the impact of ESM on job performance. Few studies found empirical support for this perspective due to limited sample size either the difficulty of accessing the data on user behavior in ESM and their job performance. We addressed this research gap through a data-sharing agreement with a large, high-tech manufacturing enterprise with internal social media and conducted a cooperative study on the impact of employee behaviors involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Companies use the ESM platform for the communication and collaboration of their employees, which include Jive, Chatter, DingTalk, Slack, IBM Connections, and Yammer. ESM usage by companies has a core trend for business activities [22], [28]. For instance, the allure of these emerging technologies is an increased capability to promote the communication and collaboration of employees within enterprises [26], [29], [30].…”
Section: Literature Review a Esm Usage In The Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…Companies use the ESM platform for the communication and collaboration of their employees, which include Jive, Chatter, DingTalk, Slack, IBM Connections, and Yammer. ESM usage by companies has a core trend for business activities [22], [28]. For instance, the allure of these emerging technologies is an increased capability to promote the communication and collaboration of employees within enterprises [26], [29], [30].…”
Section: Literature Review a Esm Usage In The Workplacementioning
confidence: 99%
“…These ESM-related functionalities will only be useful if users have the ability to properly explore and use ESM functionalities. Previous surveys have given limited consideration to individual capacities with associated ESM usage [22]- [24]. This shortcoming has encouraged us to investigate the role of digital fluency in the ESM technology.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous researchers pointed out its nature of the community of practice, extant empirical studies focused on individuals' reported behavior rather than actual practices in ESM sites [27,28]. No studies considered actual and workrelated practices and their enablers in ESM communities.…”
Section: B Theoretical Implicationsmentioning
confidence: 99%
“…Leonardi and his colleagues termed the new phenomenon enterprise social media (ESM) and found that ESM can promote emergent practices of knowledge collaboration by increasing the visibility of the network and content [16][17][18][19][20][21][22]. Against this background, ESM is expected to become an active place for CPS through establishing a virtual community of practice within organizations [23][24][25][26][27][28]. How CPS emerges in ESM communities becomes an open question.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation